2016
DOI: 10.1371/journal.ppat.1006069
|View full text |Cite
|
Sign up to set email alerts
|

Type 1 Interferons and NK Cells Limit Murine Cytomegalovirus Escape from the Lymph Node Subcapsular Sinus

Abstract: Cytomegaloviruses (CMVs) establish chronic, systemic infections. Peripheral infection spreads via lymph nodes, which are also a focus of host defence. Thus, this is a point at which systemic infection spread might be restricted. Subcapsular sinus macrophages (SSM) captured murine CMV (MCMV) from the afferent lymph and poorly supported its replication. Blocking the type I interferon (IFN-I) receptor (IFNAR) increased MCMV infection of SSM and of the fibroblastic reticular cells (FRC) lining the subcapsular sinu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 55 publications
1
23
0
Order By: Relevance
“…Innate immune pressure may also limit the efficiency of CMV spread. Important differences in routes of infection and hosts notwithstanding, murine CMV studies have revealed that macrophages and natural killer cells induce a bottleneck and restrict systemic spread from the draining lymph nodes after inoculation by footpad injection (33,34). While vaccines that induce neutralizing antibodies may prevent infection of cells altogether, other vaccines, such as those that induce T-cell or antibody-dependent cell-mediated cytotoxicity responses, allow viral replication and antigen expression within at least one cell prior to virus elimination (35,36).…”
Section: Discussionmentioning
confidence: 99%
“…Innate immune pressure may also limit the efficiency of CMV spread. Important differences in routes of infection and hosts notwithstanding, murine CMV studies have revealed that macrophages and natural killer cells induce a bottleneck and restrict systemic spread from the draining lymph nodes after inoculation by footpad injection (33,34). While vaccines that induce neutralizing antibodies may prevent infection of cells altogether, other vaccines, such as those that induce T-cell or antibody-dependent cell-mediated cytotoxicity responses, allow viral replication and antigen expression within at least one cell prior to virus elimination (35,36).…”
Section: Discussionmentioning
confidence: 99%
“…NK and NKT cells are an essential effector arm of innate immunity that participates in the control of viral infections [42][43][44][45]. IL-10 has been shown to promote NK cell proliferation, cytokine production, and cytotoxicity in vitro [46][47][48][49][50], although in some in vivo settings it could modulate NK cell activity [51,52].…”
Section: Early Il-10 Induction and Effects On Innate Immunitymentioning
confidence: 99%
“…Thus, counting of red and green plaques reveals the extent of viral passage through cre ϩ cells. SSM express lysM (14) and CD11c (29), and DC express CD11c but rarely express lysM (30). MHV-RG passing from noses to SCLN switches more in CD11c-cre than in lysM-cre mice (19), consistent with DC providing the main route to B cells (13).…”
Section: Ifnar Blockade Does Not Change the Predominant Route Of Inmentioning
confidence: 79%
“…3a, SSM are not detectably CD11c ϩ , their lower level expression level is evident only at a high magnification ( Fig. 4a) (29), and the CD11c hi cells visible in LN at a low magnification are predominantly DC. Both anti-IFNAR-treated and control LN contained CD11c ϩ GFP ϩ cells, but the former had significantly more of these cells.…”
Section: Ifn-i Protects the Nasal Respiratory Epitheliummentioning
confidence: 84%